2017
DOI: 10.18632/oncotarget.23714
|View full text |Cite
|
Sign up to set email alerts
|

Identification and preclinical evaluation of the small molecule, NSC745887, for treating glioblastomas via suppressing DcR3-associated signaling pathways

Abstract: The small-molecule naphtha [2,3-f]quinoxaline-7,12-dione (NSC745887) can effectively inhibit the proliferation of various cancers by trapping DNA-topoisomerase cleavage. The aim of this study was to elucidate cellular responses of NSC745887 in human glioblastoma multiforme (GBM, U118MG and U87MG cells) and investigate the underlying molecular mechanisms. NSC745887 reduced the cell survival rate and increased the sub-G1 population in dose- and time-dependent manners in GBM cells. Moreover, NSC745887 increased e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Based on its neutralizing effects on CD95L, LIGHT, and TL1A, DcR3 can be defined as an immunomodulator 17 , 20 , since CD95L and LIGHT induce apoptosis and inflammation, and TL1A is a T cell costimulator. DcR3’s overexpression was found in various malignant cells such as RCC cell 24 , Gliomas cell 25 , Glioblasomas cell 26 . Experimental findings by Weissinger et al 25 and Roth et al 8 suggest that DcR3 binds with CD95L and neutralizes CD95L chemo-tactic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Based on its neutralizing effects on CD95L, LIGHT, and TL1A, DcR3 can be defined as an immunomodulator 17 , 20 , since CD95L and LIGHT induce apoptosis and inflammation, and TL1A is a T cell costimulator. DcR3’s overexpression was found in various malignant cells such as RCC cell 24 , Gliomas cell 25 , Glioblasomas cell 26 . Experimental findings by Weissinger et al 25 and Roth et al 8 suggest that DcR3 binds with CD95L and neutralizes CD95L chemo-tactic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Functional effects of the risk variants in the regulation of these genes are likely, even if the mechanisms of action still are to be further explored [40]. The mechanism of function in the genetic variant in RTEL is yet to be understood, and there are several other plausible genes in the chromosomal area that could be the actual gene with functional effect such as STMN3 suggested by Labreche et al, or DcR3, a gene that has been differentially expressed in glioma and suggested as a therapeutic target by preclinical studies [41,42].…”
Section: Idh-wildtype Glioma Risk Variantsmentioning
confidence: 99%
“…Recently, Fann et al 183 evaluated the small molecule, NSC745887, in glioblastoma cells and found that it caused high expression of γH2AX, leading to DNA fragmentation, enhanced G2-M arrest, and apoptosis via induction of DNA damage responses.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%